Q and A with Dr Marianne Colbran on Crime and Investigative Reporting in the UK - Colbran, Marianne P. (2022)
We speak to Dr Marianne Colbran about her new book, Crime and Investigative Reporting in the UK, which offers an ethnographic study of UK crime news reporting over the last 40 years, covering the breakdown of relations between the Met and the mainstream media, the fallout from the 2011 phone-hacking scandal and the rise of non-profits that have the potential to repair crime journalism by reporting with – rather than on – marginalised communities. Q&A with Dr Marianne Colbran on Crime and Investigative Reporting in the UK. Policy Press. 2022